Testimoniar el vacío más allá de la catástrofe lingüística. Conjunto vacío de Verónica Gerber Bicecci (Altre Modernità, 2021)
This essay aims to analyze the novel Conjunto vacío (2015) by the argenmex visual artist Verónica Gerber Bicecci, investigating the strategies chosen by the author to testify the trauma of argentine exile in Mexico in the aftermath of the last civic-military dictatorship. Starting with some considerations about the argenmex identity, it will be shown how exile turns into a “linguistic catastrophe” (Gatti), due to the representational impossibility it imposes on the word. The problem roots in the void of sense imposed by the exile trauma, which the word always tries to fill. To give account of this void, Gerber Bicecci recurs to the mathematical theory of sets, due to its ability to conceive the void without risking filling it. The mathematical categories of sets enter the text through their graphic representations: Venn’s diagrams drawn by the author. The universal reach of the graphic code allows the abstraction of the novel’s protagonist’s experience from this representational frame, which fits for the experience of every subject who suffered exile, creating a ‘community of exile’, which we will analyze through the theoretical proposals of the Italian philosopher Roberto Esposito. In the end, the tight link between written word and graphic representation will justify the qualification of Conjunto vacío in terms of ‘multimedia testimony’.